2021
DOI: 10.1016/j.paid.2021.111111
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and human flourishing: The moderating role of gender

Abstract: COVID-19 fear restricts human freedom and decreases human flourishing. This paper examines the relationship between COVID-19 fear and human flourishing. Additionally, it tests gender's moderating effect in this relationship. Although studies show the relationship between COVID-19 fear and human flourishing, this study is a first attempt to determine gender's moderating role. Data were obtained from 326 hotel staff in the United States and analyzed using structural equation modeling and hierarchical regression.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 44 publications
2
11
1
2
Order By: Relevance
“…Unlike a cross-sectional study in the United States that found that COVID-19 fear significantly decreased human flourishing and that gender moderated the relationship between those two variables [15], people from our sample showed average levels of flourishing. Longitudinal research may also support our findings.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Unlike a cross-sectional study in the United States that found that COVID-19 fear significantly decreased human flourishing and that gender moderated the relationship between those two variables [15], people from our sample showed average levels of flourishing. Longitudinal research may also support our findings.…”
Section: Discussioncontrasting
confidence: 99%
“…Some examples of its statements are "I feel that I'm a person of worthy, at least on an equal plane with others" and "On the whole, I am satisfied with myself." After reversing five items and summing the total score, responses are classified into low [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25], medium [26][27][28][29], and high (30-40) levels of self-esteem. In this study, this scale showed a reliability of 0.85.…”
Section: Self-esteem Scalementioning
confidence: 99%
See 1 more Smart Citation
“…Anxiety prevalence, based on the aforementioned parameters, was ~20.2 to 71.3% (Makhashvili et al, 2020 ; Newby et al, 2020 ; Passos et al, 2020 ; Vujčić et al, 2021 ). Although studied less frequently, similar decreases were found when measuring flourishing (e.g., Kavčič et al, 2021 ; Sürücü et al, 2021 ; VanderWeele et al, 2021 ).…”
Section: Introductionsupporting
confidence: 54%
“…The unpredictability, uncertainty tolerance, and overloading of information during COVID-19 caused worries, fear, insecurity, and psychological stress ( Exner-Cortens et al, 2021 ; Tetreault et al, 2021 ). The lockdown, social distancing, and home confinement brought about self-isolation and loneliness, resulting in reductions in life satisfaction and flourishing ( Duong, 2021 ; Sürücü et al, 2021 ). Meanwhile, emerging research has found that physical activity exerted advantageous effects on physical and psychological well-being during the COVID-19 epidemic ( Randall et al, 2021 ), but little is known about how people’s well-being benefits from their engagement in physical activity.…”
Section: Introductionmentioning
confidence: 99%